PENGARUH RETURN ON ASSETS (ROA), DEBT TO EQUITY RATIO(DER), CURRENT RATIO (CR), RETURN ON EQUITY (ROE), PRICE EARNING RATIO (PER), TOTAL ASSETS TURNOVER (TATO), DAN EARNING PER SHARE (EPS) TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Nafisah, Nila Izatun; Halim, Abdul; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to test and explain partially and dominantly the influence of ROA, DER, CR, ROE, PER, TATO and EPS on Company Value (Tobins'Q). The sample of this research is manufacturing companies for two consecutive years, namely 2014 to 2015, amounting to 36 companies using purposive sampling method. Data analysis techniques using Multiple Linear Regression Analysis, which consists of ROA on firm value (Tobins'Q), DER on Tobins'Q, CR on Tobins'Q, ROE on Tobins'Q, PER on Tobins'Q, TATO on Tobins' Q, and EPS against Tobins'Q. The analysis shows that ROA has a positive and significant effect on Tobins'Q, DER has a significant and significant effect on Tobins'Q, CR has a positive and significant effect on Tobins'Q, ROE has no effect on Tobins'Q, PER has a positive and significant effect on Tobins' Q, TATO has a positive and significant effect on Tobins'Q and EPS has a positive and significant effect on Tobins'Q. And PER is the most dominant variable against Tobins' Q.